Uterine endometrioid adenocarcinoma with pilomatrix-like differentiation: A case report and review of the literature - L. Rusnell; Z. Al-Shamma; S.P. Bisch (Gynecologic Oncology Reports)
Introduction: We present a rare case of uterine pilomatrix-like high grade endometrioid carcinoma (PiMHEC). We provide a thorough review of the 16 other PiMHEC cases reported to date, overview of our index case, and considerations for therapeutic approach with a focus on molecular subtyping. Case Summary: This 44-year-old patient presented with widespread metastatic disease at time of diagnosis and initial clinical improvement with combination chemoradiotherapy. Immunotherapy was initiated later in the clinical course and the patient ultimately died of their disease 6 months post-diagnosis. Conclusion: Future clinicians may utilize PiMHEC case reports to formulate a therapeutic regimen and consider early initiation of immunotherapy.